Web crippling behaviour of cold-formed steel channel sections with web holes subjected to interior-one-flange loading condition – Part II: parametric study and proposed design equations. (May 2017) - Lian, Ying; Uzzaman, Asraf; Lim, James B.P.; Abdelal, Gasser; Nash, David; Young, Ben
Abstract: A parametric study of cold-formed steel sections with web openings subjected to web crippling under interior-one-flange (IOF) loading condition is undertaken, using finite element analysis, to investigate the effects of web holes and cross-sections sizes. The holes are located either centred beneath the bearing plate or with a horizontal clear distance to the near edge of the bearing plate. It was demonstrated that the main factors influencing the web crippling strength are the ratio of the hole depth to the depth of the web, the ratio of the length of bearing plate to the flat depth of the web and the location of the holes as defined by the distance of the hole from the edge of the bearing plate divided by the flat depth of the web. In this study, design recommendations in the form of web crippling strength reduction factor equations are proposed, which are conservative when compare with both the experimental and finite element results. Highlights: A parametric study of cold-formed steel sections with web openings was performed. Web crippling strength without openings are compared with current design codes. The reliability of the proposed design rules was evaluated using reliability analysis. Web crippling strength reduction factor equations are proposed.